Tinjauan Terhadap Upaya Ahli Waris Perempuan Dalam Memperoleh Hak Waris Pada Sistem Waris Adat Bali - Vella Septia Renanda; Azzahra Sania Wahyu (Lembaga Pengembangan Kinerja Dosen, 2024)
The Indonesian nation has very diverse tribes, cultures, languages ​​and religions because it has many islands. Each region certainly has its own traditions, customary laws and traditional communities and the Indonesian state recognizes the existence of customary laws within the community. The kinship system influences a rule in customary law. In Bali, the distribution of inheritance is based on a patrilineal kinship system, where in this system the son is the one who continues the family and is prominent. This research discusses the female inheritance system in Bali in Balinese customary law. We conducted research with the aim of exploring the position of female heirs in the traditional inheritance system in Bali and to find out and analyze the efforts made by female heirs to obtain inheritance rights. We use a research method, namely a qualitative approach, which means providing an explanation of the position of heirs in narrative form.